Reversible inactivation of water and sodium transport systems in frog urinary bladder and skin in the presence of detergents - Natochin YuV; Shakhmatova, E I; Bakos, P (Physiologia Bohemoslovaca, 1990)
Detergents (Triton X-100, dodecyl sulphate, saponin) added in concentrations of 0.1-10 mg/ml to solution at the outer frog skin surface reversibly reduced potential difference (PD) and short-circuit current (Isc); when added at the inner surface. Triton X-100 initially induced a short increase in the PD and Isc followed by a pronounced decrease similarly as after the application of any of the detergents used. When added to either serosal or mucosal surface of frog urinary bladder, the detergents reversibly abolished the reactivity to vasopressin. Triton X-100 blocked foskolin and cAMP-induced effects on membrane water permeability. The results suggest that hydrophobic elements of membrane play a crucial role in the regulation of membrane permeability for ions and water and of the responsiveness of the cells to vasopressin. Differences in sensitivity to detergents could be observed between the apical and the basolateral cell membrane.
Keywords: Sodium; draslík; techniky in vitro; povrchově aktivní látky; osmóza; saponiny; Potassium; Sodium Dodecyl Sulfate; Surface-Active Agents; Potassium Channels; Dose-Response Relationship, Drug; kůže; permeabilita buněčné membrány; Octoxynol; močový měchýř; Rana temporaria; zvířata; draslíkové kanály; Polyethylene Glycols; Saponins; dodecylsíran sodný; biologický transport; detergenty; Cell Membrane Permeability; voda; Urinary Bladder; sodík; oktoxynol; In Vitro Techniques; vztah mezi dávkou a účinkem léčiva; Osmosis; Animals; Water; polyethylenglykoly; Detergents; Skin; Biological Transport